The Phenomenon of Suicide Among College Students: An Analysis of the Hadith on Eschatological Consequences from the Perspective of Islamic Education - Dhofirul Yahya (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The phenomenon of suicide among university students is a serious problem that is receiving increasing attention, not only from a psychological and sociological perspective, but also from Islamic studies. This article aims to analyze the hadiths of the Prophet Muhammad SAW that explain the eschatological consequences of suicide and examine their implications from the perspective of Islamic Education as a preventive and educational effort. This study uses a qualitative method with a library research approach. Data were obtained from primary sources in the form of authentic hadith books, especially the narrations of Imams al-Bukhari, Muslim, and al-Tirmidhi, as well as secondary sources in the form of hadith commentary books, books, and relevant scientific articles. Data analysis was carried out through a study of the sanad and matan of the hadith, interpretation using the ma'ānī al-ḥadīṡ approach, and pedagogical reinterpretation within the framework of Islamic Education. The results of the study indicate that the hadiths about suicide have authentic sanad and firmly classify suicide as a major sin with the threat of severe punishment in the afterlife. However, scholars interpret the concept of